Bibliometrics-guided cyberpharmacology and transcriptomics for multidimensional analysis of the antihepatic fibrosis mechanism of kaempferol - Liu, Jiali; Song, Xiaowen; Song, Xinni; Fu, Xinyue; Niu, Shufang; Chang, Hong; Shi, Songli; Yang, Meiqing; Zhao, Ruiqi; Wang, Peng; Qi, Jun; Bai, Wanfu (Frontiers in Molecular Biosciences, 2025)
IntroductionHepatic Fibrosis (HF), a pathological remodeling process triggered by persistent liver damage, is marked by the excessive buildup of extracellular matrix (ECM), leading to a gradual deterioration of liver function and an increased likelihood of advancing to cirrhosis and liver failure.MethodsThis study adopts a systematic pharmacology methodology, initially employing bibliometric analysis to identify traditional Chinese medicine (TCM) formulations and individual herbs with potential anti-HF properties. Subsequently, a multi-dimensional network analysis is conducted to pinpoint core active components. Experimental investigations involve the construction of a carbon tetrachloride (CCl4)-induced rat model of liver fibrosis, complemented by transcriptomic technology to systematically elucidate the mechanisms of action of the active components in TCM.ResultsIn this study, kaempferol (KA), identified as the principal active compound with anti-fibrotic properties, was selected from traditional Chinese medicine (TCM) and TCM prescriptions through a combination of bibliometric analysis and network pharmacology. Pharmacodynamic evaluations, including pathological section analyses, demonstrated that KA effectively mitigated the fibrotic process and decreased collagen deposition. Further corroborated by ELISA experiments, kaempferol exhibited pronounced anti-fibrotic effects, inhibited inflammatory responses, restored liver function indices, and ameliorated the progression of liver fibrosis. Mechanistic investigations revealed that KA modulated fatty acid metabolism, retinol metabolism, and arachidonic acid metabolism by regulating the expression of key metabolic enzyme genes such as SCD, SCD2, FADS2, and CYP4A8, and significantly influenced the activity of the PPAR signaling pathway. Additionally, it impacted the dysregulation of lipid metabolism and inflammatory response pathways, significantly inhibited hepatic stellate cell (HSC) activation, and reduced ECM accumulation.DiscussionThis finding elucidates the mechanism by which KA attenuates HF through multi-target regulation, and provides a theoretical basis for metabolic reprogramming-based therapeutic strategies with translational valu.